आधुनिक राजकीय नेतारः भागः-1 - (:unkn) unknown (Kavikulguru Kalidas Sanskrit Vishwavidyalaya Ramtek Nagpur Maharashtra, 2004)
This is a Bal sahitay in Sanskrit. Aadhunik Rajkiya Neta Yaswan Rao Chouhan, Dr. Panjabrao Deshmukh, Rajiv Gandhi, and Shrikant Jichkar Biography is in this Book.
Aadhunik Rajkiya Netarah Bhagah-1
Keywords: Children's literature; Sanskrit